Radiation resistance of glasses and of solids which contain oxy'gen; Russian Physics Journal; Vol. 18, iss. 5 - Vorobyev А. А. Alexander Akimovich; Zavadovskaya E. K.; Starodubtsev V. A. Viacheslav Alekseevich; Vakhromeev V. G.; Boev S. G.; Sal'nikov V. N. (1975, 1975)
Title screen